The future of global immunisation strategies: an examination of vaccines - V. Basil Hans (International Journal of Vaccines, 2026)
Vaccination is still one of the best ways to improve public health, but worldwide immunization plans are facing new scientific, societal, and logistical problems. This article looks at the future of global immunization programs by looking at present and new vaccine technology, delivery systems, and policy frameworks. It looks at new technologies including mRNA platforms, thermostable vaccines, and new ways to distribute vaccinations that could help more people get them and respond better to new infectious diseases. The essay also looks at the ongoing problems that make it hard for everyone to get vaccinated such as vaccine hesitancy, problems with the supply chain, and differences between high-income and low-income nations. It is important to increase global readiness for future pandemics by emphasising the need of international cooperation, data-driven surveillance, and flexible decision making. The paper contends that the amalgamation of scientific innovation, ethical considerations, and public health governance is crucial for developing sustainable and resilient immunization programs to mitigate the global disease load. To develop vaccination programs that are fair, successful, and equipped to deal with both present and future global health risks, we need to understand how these things work.
Keywords: BCG; COVID-19 vaccine; immunization; public health messages; vaccines